Experimental study of multi-layer folded truncated structures under dynamic crushing - Li, Z.; Chen, Wensu; Hao, Hong; Cui, J.; Shi, Y. (PERGAMON-ELSEVIER SCIENCE LTD, 2019)
© 2019 Elsevier Ltd Dynamic crushing responses of multi-layer folded truncated sandwich structures are investigated experimentally in this study. The proposed structures are folded from aluminium thin sheets, forming open-top truncated pyramids with square and triangular base shapes. The folded structures are then stacked into a multi-layer sandwich panel by implementing 3 mm thick plate in-between foldcores with thread rods used as guide of movement during deformation. No bonding is applied between any parts of the sandwich structure, which allows the easy replacement of deformed core after crushing. Two shapes of folded structures, i.e. Truncated Square Pyramid (TSP)and Truncated Triangular Pyramid (TTP)are used as the foldcores to form sandwich panels. Specimens are crushed under different velocities. The testing data are compared to those obtained under quasi-static loading condition. Uniform load-displacement response with very low initial crushing peak force is observed for TSP foldcore under different loading rates, where the initial peak crushing force of TTP foldcore is slightly more sensitive to crushing velocity. Different damage modes of TSP are observed with the change of crushing velocity which is consistent with the previous numerical results of this folded structure. Multi-layer TSP foldcore with lower volumetric density is also studied under dynamic loading condition.